Δϕ distributions between final state particles as a criterion of the pile-up background mismodeling and its impact on Z(vv)γ process. (December 2020) - Pyatiizbyantseva, D; Soldatov, E Yu
Abstract: In the case of the pile-up background (background from the neighboring interactions inside the bunch crossing) for Z ( vv ) γ process at the Large Hadron Collider (LHC) experiments, its accurate calculation is very challenging. If the impact of the pile-up background is negligible, as it is expected in the case of Z ( vv ) γ process selection, some global uncertainty from this source can be used. This report studies the pile-up background and shows that it is expected to have a completely different shape for Δ ϕ distributions between final state particles in comparison to the signal and other background processes. Thus, the absence of Δ ϕ -mismodeling in the analysis proves that the pile-up background is indeed negligible.